Clinical practice change requires more than comparative effectiveness evidence: abdominal aortic aneurysm management in the USA. (January 2012) - Ballard, David J; Filardo, Giovanni; Graca, Briget da; Powell, Janet T
Adoption of healthcare innovations frequently outpaces the evidence of effectiveness. Endovascular repair (EVAR) for abdominal aortic aneurysms in the USA demonstrates how comparative effectiveness research without evidence-based reimbursement changes may fail to influence clinical practice. Randomized controlled trials for small abdominal aortic aneurysms demonstrate no lasting benefits of EVAR or open surgical repair (OSR) compared with surveillance, and for large abdominal aortic aneurysms demonstrate no lasting survival benefit of EVAR over OSR, and do show poorer durability and higher costs for EVAR. Nonetheless, >50% of elective abdominal aortic aneurysm repairs in the USA use EVAR. Factors that may be driving the high use of EVAR include patient preference, surgeons'' desire to appear 'up-to-date'' in the procedures they offer, higher hourly surgeon reimbursement for EVAR than OSR, and the expansion of physician specialties able to perform abdominal aortic aneurysm repair from only vascular surgeons with OSR, to vascular surgeons and interventional radiologists/cardiologists with EVAR. By comparison, in Canada, where government health insurance restricts EVAR coverage to high surgical risk patients, only approximately 25% of abdominal aortic aneurysm repairs are performed using EVAR. Country-specific cost studies and a prospective population-based study collecting detailed clinical data to identify patient subgroups that truly benefit from a particular management strategy are needed to inform policy regarding EVAR availability and reimbursement.